INSTRUMEN PENILAIAN TERINTEGRASI : PENGUKURAN KEMAMPUAN BERPIKIR KRITIS DAN KETERAMPILAN SAINS SISWA PADA MATERI LARUTAN ELEKTROLIT DAN NONELEKTROLIT - Sri Rejeki Dwi Astuti; Anggi Ristiyana Puspita Sari; Rizki Nor Amelia; Karlinda Karlinda (UIN Sumatera Utara Medan, 2022)
This study aimed to explore the characteristics of the tests used in measuring students' abilities such as item fit, item difficulty level, and test reliability and to measure students’ ability in electrolyte test takers' reliability, and person misfit. This research involved 260 students from two senior high schools in Bantul, Yogyakarta. The research instruments was integrated assessment instrument for electrolyte and nonelectrolyte solution matter consisted of 8 essay question. The data were analyzed with Rasch model using Winstep software version 3.73. The results revealed that all items on the integrated assessment instrument have been proven to be fit with Rasch model, have good test reliability, and have good difficulty level parameters. Moreover, students' abilities were obtained very diverse, i.e. very low, low, medium, high and very high abilities. Meanwhile, the person reliability were very low and 48 students were identified as person misfit . Thus, further examination can be conducted, so that students who are identified as misfit s can obtain guidance from the teacher.